Epitafium nagrobne biskupa Andrzeja Szołdrskiego z katedry poznańskiej w świetle jego testamentu (Bishop Andrzej Szołdrski’s Tombstone Epitaph from the Poznań Cathedral in the Light of His Will) - Barbarzak, Dawid (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2024)
The Latin tombstone inscription dedicated to Andrzej Szołdrski, the bishop of Poznań (c. 1583–1650), mainly commemorates the work of rebuilding the cathedral destroyed in a fire in 1622, as well as his generous donations for church and charity purposes. A comparison of the inscription with the bishop’s will reveals many similarities between both texts. The fact that the authors of the inscription were also the executors of the will greatly influenced the content of the epitaph, as well as the entire appearance of the chapel. Both texts contain typical Baroque concepts related to the passing of time (vanity, theatrum mundi). However, while the bishop downplays the role of his earthly achievements in the will, the epitaph, according to the tradition of this epigraphic genre, belongs to enkomion (laudatio).